1999
DOI: 10.1200/jco.1999.17.8.2341
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial of Docetaxel Versus Doxorubicin in Patients With Metastatic Breast Cancer

Abstract: Crown for the 303 Study GroupPurpose: This phase III study compared docetaxel and doxorubicin in patients with metastatic breast cancer who had received previous alkylating agent-containing chemotherapy.Patients and Methods: Patients were randomized to receive an intravenous infusion of docetaxel 100 mg/m 2 or doxorubicin 75 mg/m 2 every 3 weeks for a maximum of seven treatment cycles.Results: A total of 326 patients were randomized, 165 to receive doxorubicin and 161 to receive docetaxel. Overall, docetaxel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
262
2
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(279 citation statements)
references
References 26 publications
9
262
2
6
Order By: Relevance
“…Combining the results of this study with the two published reports DaunoXome has shown objective responses in eight out of 35 (23%) evaluable patients (Anonymous, 1996;Darskaia et al, 1999). The response rate for this relatively non-toxic anthracycline based therapy must be taken in context with those reported for single-agent doxorubicin which vary from 30 -34% in recent randomised phase III studies (Henderson et al, 1989;Sledge et al, 1997;Chan et al, 1999;Norris et al, 2000). The overall time to tumour progression of 5 months (8.5 months in those patients treated at 120 and 150 mg m 2 ) and median survival of 13.75 months are in keeping with the results reported for large randomised studies of doxorubicin when used alone or as part of a combination regimen in the treatment of symptomatic relapsed breast cancer (Norris et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Combining the results of this study with the two published reports DaunoXome has shown objective responses in eight out of 35 (23%) evaluable patients (Anonymous, 1996;Darskaia et al, 1999). The response rate for this relatively non-toxic anthracycline based therapy must be taken in context with those reported for single-agent doxorubicin which vary from 30 -34% in recent randomised phase III studies (Henderson et al, 1989;Sledge et al, 1997;Chan et al, 1999;Norris et al, 2000). The overall time to tumour progression of 5 months (8.5 months in those patients treated at 120 and 150 mg m 2 ) and median survival of 13.75 months are in keeping with the results reported for large randomised studies of doxorubicin when used alone or as part of a combination regimen in the treatment of symptomatic relapsed breast cancer (Norris et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As a single agent, docetaxel has shown marked clinical activity in the treatment of anthracycline-resistant and chemotherapy-naïve (for metastatic disease) breast cancer, achieving response rates of 34 and 50 -72%, respectively (Ravdin et al, 1995;Valero et al, 1995;Marty et al, 1997;Valero, 1997). In a randomised phase III trial in first-line metastatic breast cancer docetaxel (100 mg m À2 ) exhibited superior efficacy and tolerability compared with doxorubicin (at the optimal dose of 75 mg m À2 ) (Chan et al, 1999). The role of docetaxel (both as a single agent and in combination) in early or locally advanced breast cancer is currently being investigated (Gradishar, 1997;Mamounas, 1998;Costa et al, 1999).…”
mentioning
confidence: 99%
“…A recent large randomised trial demonstrated improved survival with docetaxel compared with combination therapy with mitomycin C plus vinblastine in patients with MBC who had progressed despite prior anthracycline-containing chemotherapy (Nabholtz et al, 1999). In another multicentre, randomised phase III trial a higher response rate was observed with docetaxel (47.8%) compared with doxorubicin (33.3%) in patients with MBC who had received prior alkylating agent-containing chemotherapy (Chan et al, 1999).…”
Section: Docetaxel Plus Fec In Metastatic Breast Cancer M Spielmann Ementioning
confidence: 94%
“…The anthracyclines have long been considered to be the most active agents in MBC, with reported response rates of about 50% for monotherapy (Findlay and Walker-Dilks, 1998;Ormrod et al, 1999). Of the newer agents now available, docetaxel (Taxotere), a semi-synthetic taxoid, has shown the most promising activity of all the compounds used so far in MBC, even in anthracycline-resistant tumours (Van Oosterom, 1995;Bonneterre et al, 1999;Chan et al, 1999;Nabholtz et al, 1999;Sjöström et al, 1999). Several phase III trials have now established docetaxel as the most active single agent in MBC (Chan et al, 1999;Nabholtz et al, 1999).…”
mentioning
confidence: 99%